2006
DOI: 10.1038/nn1680
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and synaptic removal of NR3A-containing NMDA receptors by PACSIN1/syndapin1

Abstract: A key step in glutamatergic synapse maturation is the replacement of developmentally expressed N-methyl-D-aspartate receptors (NMDARs) with mature forms that differ in subunit composition, electrophysiological properties and propensity to elicit synaptic plasticity. However, the mechanisms underlying the removal and replacement of synaptic NMDARs are poorly understood. Here we demonstrate that NMDARs containing the developmentally regulated NR3A subunit undergo rapid endocytosis from the dendritic plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
203
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(227 citation statements)
references
References 49 publications
24
203
0
Order By: Relevance
“…Pacsin1 binds to NR3A-containing NMDA receptors and promotes their endocytosis (39), and Synaptojanin1 has also been implicated in endocytosis (40), specifically in postsynaptic AMPA receptor downregulation (41). Pak5 −∕− ∕Pak6 −∕− mice exhibit defects in locomotion, learning, and memory (16), and based on our results, we propose that the cognitive and behavioral deficits observed in these mice may be partly attributable to altered endocytosis and vesicle trafficking.…”
Section: Discussionsupporting
confidence: 56%
“…Pacsin1 binds to NR3A-containing NMDA receptors and promotes their endocytosis (39), and Synaptojanin1 has also been implicated in endocytosis (40), specifically in postsynaptic AMPA receptor downregulation (41). Pak5 −∕− ∕Pak6 −∕− mice exhibit defects in locomotion, learning, and memory (16), and based on our results, we propose that the cognitive and behavioral deficits observed in these mice may be partly attributable to altered endocytosis and vesicle trafficking.…”
Section: Discussionsupporting
confidence: 56%
“…The biology of PACSIN1 overlaps heavily with known pathways affected in Huntington disease, namely the recycling of NMDA receptors (19) and the formation of neuronal spines (21). PACSIN1 is known to directly interact with human huntingtin within the polyproline region (18), and we have additionally shown that PACSIN1 interacts with the N17 domain.…”
Section: Measuring the Conformation Of The Amino Terminus Within Thementioning
confidence: 72%
“…This interaction is enhanced in the presence of expanded polyglutamine (18). PACSIN1 is a predominantly cytoplasmic neuronal protein that has functions in NMDA receptor recycling (18,19), actin/microtubule reorganization (20), and neuronal spine formation (21). Both N17 and PACSIN1 are substrates of casein kinase 2 (CK2) (12,17).…”
mentioning
confidence: 99%
“…PACSIN1 is a neuronal-specific protein that regulates activitydependent retrieval of synaptic vesicles in the presynaptic terminals (19)(20)(21)(22) as well as the endocytosis of the NR3A subunit of NMDA receptors on the postsynaptic membrane (23). More importantly, PACSIN1 has been implicated in various neurodegenerative disorders, including Huntington and Alzheimer's diseases (24,25).…”
Section: Syndapin | Receptor Traffickingmentioning
confidence: 99%